Measuring Competitiveness in a World of Global Value Chains - Bayoumi, Tamim (IMF Working Papers; Working Paper, 2018)
All common real effective exchange rate indexes assume trade is only in final goods, despite the growing presence of global supply chains. Extending effective exchange rate indexes to include such intermediate goods can imply radically different effective exchange rate weights, depending on the relative substitutability of goods in final demand and in production. Unfortunately, the effect of these shifts in weights are difficult to identify empirically because the two currencies most affected-the dollar and the renminbi-have moved closely together. As the renminbi becomes more flexible, however, it will be important to determine which assumptions are the most realistic.